2012
DOI: 10.1088/1468-6996/13/6/064204
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of DNA-antibody–apatite composite layers for cell-targeted gene transfer

Abstract: Surface-mediated gene transfer systems using apatite (Ap)-based composite layers have received increased attention in tissue engineering applications owing to their safety, biocompatibility and relatively high efficiency. In this study, DNA-antibody-apatite composite layers (DA-Ap layers), in which DNA and antibody molecules are immobilized within a matrix of apatite nanocrystals, were fabricated using a biomimetic coating process. They were then assayed for their gene transfer capability for application in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Yazaki et al [ 156 ] co-immobilized DNA and antibodies within a hydroxyapatite matrix and assessed the obtained materials’ cell-specific gene transfer. They observed the transfection of CD49f-positive CHO-K1 cells in the presence of an anti-CD49f antibody.…”
Section: Nanocarriers For the Delivery Of Nucleic Acids And Proteimentioning
confidence: 99%
“…Yazaki et al [ 156 ] co-immobilized DNA and antibodies within a hydroxyapatite matrix and assessed the obtained materials’ cell-specific gene transfer. They observed the transfection of CD49f-positive CHO-K1 cells in the presence of an anti-CD49f antibody.…”
Section: Nanocarriers For the Delivery Of Nucleic Acids And Proteimentioning
confidence: 99%
“…After conducting countless numbers of gene transfer studies, researchers identified the pros and cons of both viral and non-viral approaches. The latter is favoured by some researchers because of several advantages [18][19][20] as this approach somehow triggers low immune response compared with viral approach which makes it suitable for human therapy. 21 It was also observed that the non-viral approach caused low toxicity to cells.…”
Section: Tissue Engineering Pioneered By Langer and Vacantimentioning
confidence: 99%
“…Over the past decade, various approaches to increase the gene transfer efficiency of the DNA-CaP nanocomposite layer have been proposed. 1,[4][5][6][7] Previous approaches were based on the co-immobilization of biofunctional molecules such as cell adhesion molecules (laminin, fibronectin), 4,5 lipids, 6 and antibodies 7 within the DNA-CaP nanocomposite layer to enhance cell-layer interactions. The co-immobilization of these biofunctional molecules increased the gene transfer efficiency of the nanocomposite layer by 1-4 orders of magnitude.…”
mentioning
confidence: 99%
“…The co-immobilization of these biofunctional molecules increased the gene transfer efficiency of the nanocomposite layer by 1-4 orders of magnitude. 1,[4][5][6][7] Here we discovered another approach without biofunctional molecules that is based on kinetic control of CaP nucleation in the fabrication process of the DNA-CaP nanocomposite layer to increase its gene transfer efficiency. Nucleation of CaPs includes amorphous phase nucleation as well as crystalline phase nucleation.…”
mentioning
confidence: 99%
See 1 more Smart Citation